2021
DOI: 10.11002/kjfp.2021.28.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Quality and antioxidant properties of morning bread added with sourdough according to the mixing ratios of sea buckthorn leaf

Abstract: In this study, a natural fermentation starter formulation was developed for functional bread products by substituting baker's yeast with naturally fermented sourdough added with sea buckthorn leaf (SBL). The quality and antioxidant properties of morning bread (MB) with 0%, 10%, 20%, and 30% SBL added to sourdough were investigated. The pH of MB dough decreased when the mixing ratio (MR) of SBL was increased. The dough-raising power by incubation time (20-60 min) increased when the MR of SBL was increased. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
1
1
Order By: Relevance
“…In this study, the polyphenol and flavonoid contents in COE were measured as 424.150 mg GAE/g and 127.566 mg CE/g, respectively. Compared to the polyphenol contained in the ethanolextracted sea buckthorn leaf, which is reported to be 285.64 mg GAE/g [41], the total polyphenol amount from COE measured in this study was 1.49 times higher. Furthermore, the total flavonoid amount in this study was 2.13 times higher than the other research result, which reported 58.84 ± 0.47 mg CE/g in ethanol-extracted artichoke extract [42].…”
Section: Discussioncontrasting
confidence: 64%
“…In this study, the polyphenol and flavonoid contents in COE were measured as 424.150 mg GAE/g and 127.566 mg CE/g, respectively. Compared to the polyphenol contained in the ethanolextracted sea buckthorn leaf, which is reported to be 285.64 mg GAE/g [41], the total polyphenol amount from COE measured in this study was 1.49 times higher. Furthermore, the total flavonoid amount in this study was 2.13 times higher than the other research result, which reported 58.84 ± 0.47 mg CE/g in ethanol-extracted artichoke extract [42].…”
Section: Discussioncontrasting
confidence: 64%
“…Both the total polyphenol and flavonoid contents, as shown in Table 6 , exhibited a trend of decreasing total flavonoid content as the ethanol concentration increased. Flavonoids, as polyphenolic substances, are reported to have differences in solubility in water and ethanol based on their chemical structures [ 31 ].…”
Section: Resultsmentioning
confidence: 99%